IMPLICATIONS OF REVERSE PROOF AS AN EFFORT TO ERADICATE CRIMINAL ACTS OF CORRUPTION AND RETURN STATE ASSETS - Ardiansyah, Muh. Rustiawan (JILPR Journal Indonesia Law and Policy Review, 2024)
The crime of corruption is a large and systemic problem and is also a legal issue involving a type of crime that is complicated to overcome. One of the reasons why it is difficult to eradicate corruption is the difficulty of proving it, because the perpetrators of this crime carry out their crimes very neatly. To solve the problem of the difficulty of proving criminal acts of corruption, one of the efforts that can be taken by the government through penal means is to apply reverse evidence to corruption cases. The return of state assets corrupted by the perpetrators must be the main focus, considering that the losses and damage caused are very miserable for the people. For this reason, in connection with the description of the problem above, the author is interested in studying the dynamics of the problem of evidence in cases of criminal acts of corruption which in the end can restore maximum state assets. In this research, the method used is a normative legal research method with a literature study approach with a focus on legal studies which is linked to the effectiveness of reverse evidence. The results of the research are that the evidence in the corruption trials of the four corruption cases has referred to the dimension of mutual proof or balanced evidence between the Public Prosecutor and the defendant, but has not yet maximally applied limited and balanced reverse evidence. So the evidence applied is evidence of a general nature and is based on the theory of negative evidence based on law (negatief wettelijk bewijstheorie), which is regulated in Article 183 of the Criminal Procedure Code.